Isolation and Characterization of an Adult Stem Cell Population from Human Epidural Fat. (17th March 2019) - Al-Jezani, Nedaa; Cho, Roger; Masson, Anand O.; Lenehan, Brian; Krawetz, Roman; Lyons, Frank G.
Abstract : Study Design . Isolation and characterization of human epidural fat (HEF) stem/progenitor cells. Objective . To identify a progenitor population within HEF and to determine if they meet the minimal criteria of a mesenchymal stem cell (MSC). Summary of Background Data . The biological function, if any, has yet to be determined for HEF. The presence of MSCs within HEF may indicate a regenerative potential within the HEF. Methods . HEF was isolated from 10 patients during elective spinal surgery. HEF cells were differentiated along osteo-, adipo-, and chondrogenic lineages, with differentiation analyzed via qPCR and histology. The cell surface receptor profile of HEF cells was examined by flow cytometry. HEF cells were also assayed through the collagen contraction assay. Prx1 CreERT2GFP : R26R TdTomato MSC lineage-tracking mice were employed to identify EF MSCs in vivo . Results . HEF cell lines were obtained from all 10 patients in the study. Cells from 2/10 patients demonstrated full MSC potential, while cells from 6/10 patients demonstrated progenitor potential; 2/10 patients presented with cells that retained only adipogenic potential. HEF cells demonstrated MSC surface marker expression. All patient cell lines contracted collagen gels. A Prx1 -positive population in mouse epidural fat that appeared to contribute to the dura of the spinal cord was observed in vivo . Conclusions . MSC and progenitor populations are present within HEF. MSCs were not identified in all patients examined in the current study. Furthermore, all patient lines demonstrated collagen contraction capacity, suggesting either a contaminating activated fibroblast population or HEF MSCs/progenitors also demonstrating a fibroblast-like phenotype. In vivo analysis suggests that these cell populations may contribute to the dura. Overall, these results suggest that cells within epidural fat may play a biological role within the local environment above providing a mechanical buffer.